Re-evaluated treatment outcomes of bacteriologically positive TB patients registered at a clinic in Lusaka, Zambia in 2018 - Daka, S. (Public Health Action, 2021)
SETTING: An urban TB diagnostic centre in Lusaka, Zambia. OBJECTIVE: To re-evaluate treatment outcomes of all bacteriologically confirmed TB patients registered in 2018. DESIGN: This was a retrospective cohort study on TB patients. Treatment outcomes of patients who were transferred out were retrieved. RESULTS: A total of 182 patients were registered, 26 of whom had missing documents; these were excluded from the study. Of the remaining 156 patients who were reviewed, 86 (55.1%) were correctly evaluated by the centre, 35 (22.4%) were incorrectly evaluated and 35 (22.4%) were ‘transferred out’ (not evaluated). As a result of this review, the number of evaluated patients increased from 86 (55.1%) to 150 (96.2%). The cure and treatment success rates rose from 43.6% and 44.2%, respectively, to 57.7% and 73.1%, respectively. Of note, 14 of the 35 patients who were initially declared ‘transferred out’ did not actually reach their treatment facilities and ended up being lost to follow-up. CONCLUSION: This study shows that it is possible to evaluate almost all TB patients. Re-evaluation of treatment outcomes of TB patients revealed the problems in the TB services that need to be improved in the future.